1984
DOI: 10.7589/0090-3558-20.3.212
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variations in Physiological Indices of Adult Female White-Tailed Deer in Texas

Abstract: Seasonal variations in blood chemistry, urine chemistry, fat reserves, and crude protein levels of rumen contents were determined for free-ranging adult female white-tailed deer (Odocoileus virginianus Zimmermann) in central Texas. Seasonal variations (P less than 0.05) existed for serum total protein, albumin, globulin, albumin/globulin ratios, blood urea nitrogen (BUN), cholesterol, alkaline phosphatase, creatinine, phosphorus, and sodium; and urinary urea/creatinine (U/C) ratios, rumen crude protein, the ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 18 publications
0
10
1
Order By: Relevance
“…This presence of protein fractions is different from that described by Waid and Warren [25] in adult female white-tailed deer, in which the pattern for total protein and albumin is similar, but globulins do not show a consistent seasonal trend. However, previous studies [26] have pointed out that the decrease in albumin synthesis might be a response to the increase in globulin synthesis, a statement that agrees with out results.…”
Section: Discussioncontrasting
confidence: 47%
“…This presence of protein fractions is different from that described by Waid and Warren [25] in adult female white-tailed deer, in which the pattern for total protein and albumin is similar, but globulins do not show a consistent seasonal trend. However, previous studies [26] have pointed out that the decrease in albumin synthesis might be a response to the increase in globulin synthesis, a statement that agrees with out results.…”
Section: Discussioncontrasting
confidence: 47%
“…DeLiberto et al (1989) reported that K + values were highest in the summer, while several studies have shown no seasonal variation in K + (Seal et al, 1978;Kie et al, 1983;Waid and Warren, 1984;Jopson et al, 1997). DelGiudice et al (1992) investigated seasonal effects on blood parameters of white-tailed deer and reported the most probable cause of hyperkalemia during winter was a partial renal shutdown associated with reduced circulatory volume.…”
Section: Discussionmentioning
confidence: 99%
“…Many reference ranges have been reported for potassium (K + ) in freeranging cervids (Table 1; Wilber and Robinson, 1958;White and Cook, 1974;Seal et al, 1978;Kie et al, 1983;Waid and Warren, 1984;DeLiberto et al, 1989;DelGiudice et al, 1992). The International Species Information System (ISIS), widely used as a reference for captive populations, reports a mean K + of 4.360.9 milliequivalents (mEq)/l (n561; ISIS, 2002) for white-tailed deer (Odocoileus virginianus).…”
Section: Introductionmentioning
confidence: 99%
“…Amount of kidney fat in deer varies seasonally (Finger et al 1981, Waid andWarren 1984) with higher reserves in females occurring in winter than in other seasons in the South (Deliberto et al 1989). Young animals possess lower levels of fat compared with adults (Bjarghou et al 1977, Johns et al 1984, Ballard and Whitman 1987.…”
Section: Discussionmentioning
confidence: 99%